The effect of laparoscopic sleeve gastrectomy in improving endocrinal and psychiatric comorbidities in morbidly obese adolescents: a single-center study - Mohammad Allam; Mohamed Elbarbary; Omnia Raafat Amin; Ahmed Kadry Wishahy; Marwa Ahmed Sedkey; Yomna Ahmed Hosni; Mahmoud Othman Aboudeif; Marise Abdou (Egyptian Pediatric Association Gazette)
Abstract Background Adolescent and childhood obesity are a growing epidemic resulting in a wide range of comorbidities early in life. Therefore, early awareness and management are necessary. Laparoscopic sleeve gastrectomy (LSG) is a safe and efficient technique in the management of pediatric and adolescent obesity when behavioral modification fails. This study aimed to assess the safety and effectiveness of LSG in managing obesity and improving comorbidities among adolescents. Methods Fifteen adolescent individuals underwent LSG and followed up over a 6-month duration. Excess weight loss, body mass index (BMI), endocrinal assessment and psychiatric estimation of depression, and quality of life were assessed both pre- and postoperatively up to 6 months. Results. Our cohort of patients had a mean age ± SD of 13.9 ± 1.6 years, showing a significant improvement in BMI and excess weight loss from 51.6 ± 10.2 kg/m2 to 36.7 ± 7.1 kg/m2 and 29.8 ± 14% to 58.9 ± 13%, respectively, with a significant p-value of < 0.001. Laboratory investigations showed that insulin, HOMA-IR, and HbA1c levels exhibited a statistically significant drop with a p-value < 0.001. Also, cholesterol and triglyceride levels decreased with a statistically significant p-value of < 0.001 and 0.026, respectively. However, LDL showed improvements while not reaching statistical significance. Psychiatric evaluation of the patients showed resolution of depression and improvement of the quality of life after LSG with a significant p-value of < 0.001. Conclusion LSG displayed a significant reduction in weight and improvement of comorbidities of the patients. In addition, it resulted in a significant improvement in both depressive symptoms and quality of life.